Spelling monosyllabic English words. - Khanna, Maya M; Cortese, Michael J; Hughes, Kylie; Anderson, Kayley (Quarterly Journal of Experimental Psychology, 2024)
We conducted a megastudy to examine the spelling of American English monosyllables with typewritten responses. We related both sublexical and lexical/semantic factors to spelling accuracy and reaction time (RT) for the first keypress and response duration for spelling 1,856 monophonic monosyllables. We found that (a) each of 13 predictor variables was significantly related to performance for at least one measure, (b) orthographic length was unrelated to the first key RT, but did relate to accuracy and response duration, (c) sound-spelling and spelling-sound consistency was related to performance, and in particular, onset consistency related to accuracy and first key RT, but was unrelated to response duration, (d) contextual diversity was consistently related to performance across all measures, and (e) age of acquisition (AoA) was related to all measures, but was related more to the first key RT than response duration. The results indicate that people begin the spelling process once they identify the first letter, and they continue to process the spelling pattern as the response unfolds. These results are best explained by a parallel-distributed-processing framework.